The Role of the Judiciary in Balancing State Power in National Security: A Case Study of the Use of Special Laws in Thailand - Pasanaga, Apipat (NKRAFA Journal of Humanities and Social Sciences, 2025)
In a democratic system governed by the rule of law, the exercise of state power must be subject to appropriate mechanisms of oversight and checks and balances—particularly in situations where the state enforces special security laws, such as the Emergency Decree on Public Administration in Emergency Situations B.E. 2548 (2005) and the Martial Law Act B.E. 2457 (1914), which grant the executive and state officials broad powers to restrict the rights and freedoms of the people. This article aims to examine the role of the Thai judiciary in balancing state power within such a context by analyzing relevant court judgments and comparing them with the practices of the German Federal Constitutional Court and the Supreme Court of the United States. The study seeks to formulate legal and policy recommendations and presents a critical observation as to how the Thai judiciary should reconsider its conceptual framework and legal mechanisms to ensure that the exercise of special powers does not become a tool for rights infringement, but rather a genuinely balanced mechanism grounded in the principles of the rule of law and human rights. The methodology employed includes doctrinal legal analysis of special laws, key judicial decisions, and relevant international human rights legal principles, with an emphasis on the principles of proportionality, the rule of law, and checks and balances. The findings indicate that although Thai courts have played a role in interpreting and reviewing the exercise of special powers in certain cases, in many rulings they tend to give greater weight to the justifications presented by the state than to the protection of individual freedoms. This reveals limitations in the judiciary’s effectiveness as a balancing mechanism during states of emergency. The article thus recommends the promotion of international legal standards—such as the principles of proportionality, necessity, and the least restrictive means—in judicial reasoning, as well as the reform of legal structures to allow courts greater independence in reviewing executive action. Additionally, it calls for the cultivation of a judicial culture firmly grounded in human rights, so that the judiciary may truly serve as the last line of defense for the people in times of crisis.